Traveller-Friendly Vehicle Rental Web-Based Application (TWB): A Web-Based Application to Optimize Business Efficiency - HASAN, NUR AINA NATASHA; MAT NAWI, ROSMAMALMI (Applied Information Technology And Computer Science, 2026)
Since the previous system for renting vehicles involved lots of paperwork and was inefficient, the Traveller-Friendly Vehicle Rental Web-Based Application was made to modernize it and remove these hassles. The purpose of this solution is to make things easier, more accurate, and boost productivity in the company. Knowledge from both customers and businesses pointed out the key issues and important needs that were important for the system. The main purpose of the platform was to provide better information, make the use of cars more effective, and offer top customer service which led to greater client satisfaction, more efficient operations, and a sustainable business for the rental vehicle industry. In the development phase, programmers kept testing and repairing to avoid any errors and to guarantee the application’s functionality, safety, and dependability. The completion of the project as a success came from ensuring that all features were implemented and that the platform ran smoothly and without disruption.